The Influence of Nozzle Injection Pressure on Seawater Evaporation Inside an Evaporator Tube - Aji, Ikbal Prasetiyo; Mugisidi, Dan; Yusuf, Ahmad Maulana; Heriyani, Oktarina (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2024)
Indonesia, the largest archipelagic country in the world, possesses a vast marine area. Despite being surrounded by the sea, many coastal communities in Indonesia lack access to clean water. Seawater distillation presents a viable solution to this scarcity. This process involves separating salt from seawater to produce fresh water. This study aims to analyze the effect of nozzle spray pressure on the evaporation process of seawater to optimize fresh water production. Experiments were conducted using a fogging nozzle with a diameter of 0.3 mm, varying the nozzle pressure at 40 psi, 70 psi, and 100 psi. The data were statistically analyzed to determine the impact of nozzle pressure on seawater evaporation. The results indicate that the highest evaporation occurred at a nozzle pressure of 40 psi, yielding 10 g of condensed seawater, whereas the lowest evaporation was observed at 100 psi, producing 4 g.